Analisis Performance Test Aero Turbine Rolls-Royce M250-C20B - Aldo Akbar Putra; Kritian Felix F. Purba; Mario Delon Simanjuntak; Aditia Aulia (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This article analyzes the performance of the Rolls-Royce M250-C20B turboshaft engine through a performance test conducted after a comprehensive overhaul at PT. Nusantara Turbine and Propulsion. The test was carried out to evaluate key parameters, including rotor speed (N1 and N2), exhaust gas temperature (T5), shaft horsepower (SHP), vibration levels, and specific fuel consumption (SFC). The results indicate that the engine meets operational feasibility standards with high efficiency and stable vibration performance, although some parameters were slightly below optimal thresholds. In conclusion, the engine is considered airworthy and suitable for continued operation with satisfactory and economical performance, in line with aviation industry standards.